2013
DOI: 10.1165/rcmb.2012-0198oc
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells Reduce Acute Lung Injury Fibroproliferation by Decreasing Fibrocyte Recruitment

Abstract: Acute lung injury (ALI) causes significant morbidity and mortality. Fibroproliferation in ALI results in worse outcomes, but the mechanisms governing fibroproliferation remain poorly understood. Regulatory T cells (Tregs) are important in lung injury resolution. Their role in fibroproliferation is unknown. We sought to identify the role of Tregs in ALI fibroproliferation, using a murine model of lung injury. Wild-type (WT) and lymphocyte-deficient Rag-1 2/2 mice received intratracheal LPS. Fibroproliferation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
139
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(145 citation statements)
references
References 44 publications
(58 reference statements)
4
139
1
1
Order By: Relevance
“…On day 6 after intratracheal LPS, left lungs were homogenized in 1 ml of Complete Lysis Buffer (Roche, Indianapolis, IN) using an UltraTurrax tissue homogenizer (Janke and Kunkel, Wilmington, NC). Collagen was measured by Sircol Assay (BioColor, Carrickferguss, UK) according to the manufacturer's instructions as before (18).…”
Section: Methodsmentioning
confidence: 99%
“…On day 6 after intratracheal LPS, left lungs were homogenized in 1 ml of Complete Lysis Buffer (Roche, Indianapolis, IN) using an UltraTurrax tissue homogenizer (Janke and Kunkel, Wilmington, NC). Collagen was measured by Sircol Assay (BioColor, Carrickferguss, UK) according to the manufacturer's instructions as before (18).…”
Section: Methodsmentioning
confidence: 99%
“…98 Treg participation in IPF has a somewhat conflicting history, however, with studies demonstrating both protective and causative roles in fibrosis, suggesting that further research on this promising subset of Tregs is warranted. [99][100][101][102] Markedly decreased expression of CD28, a necessary component of T-cell activation, on the surface of CD4+ T-cells was correlated with a more severe 1-year outcome in IPF. 103 These findings were supported further by genomic analysis of peripheral blood mononuclear cells from two separate IPF cohorts that showed that low expression of four genes, LCK, ITK, ICOS, and CD28, was associated with increased IPF mortality.…”
Section: T-cells: Sema7a and Cd28mentioning
confidence: 99%
“…42 Regulatory T cells (Tregs) could reduce lung fibrocyte recruitment by inhibiting the CXCL12/CXCR4 axis after acute lung injury. 58 …”
Section: Cxcl12/cxcr4 Axis Mediated Fibrocyte Trafficing In Pulmonarymentioning
confidence: 99%